Polarization as a Discriminator of Light-Absorbing Impurities in or Above Snow - Ottaviani, Matteo (Frontiers in Remote Sensing, 2022)
This conceptual paper presents advanced radiative transfer computations of the light polarization originating from a snowpack consisting of non-spherical grains and variable content of light-absorbing impurities, either embedded in the snowpack or (with the same optical properties)} lofted above it in the form of atmospheric aerosols. The results highlight the importance of considering shapes other than spherical for the snow grains, which otherwise can lead to non-negligible errors in the retrieval of snow albedo from remote sensing observations. More importantly, it is found that polarimetric measurements provide a means to partition light-absorbing impurities embedded in the snowpack from absorbing aerosols aloft, a task traditionally prohibitive for sensors capable exclusively of measurements of total reflectance. Heritage techniques to obtain snow-grain size from shortwave infrared observations of total reflectance are well established, as are those that leverage polarimetric, multi-angular observations across the entire optical spectrum to characterize optical and microphysical properties of atmospheric aerosols. The polarization signatures of near-infrared (e.g. 870 nm) observations carry critical information on snow grain shape. The prospected launch of spaceborne polarimeters with proven accuracy therefore advocates for the development of data inversion schemes, to boost the accuracy of simultaneous retrievals of atmospheric and surface parameters in polar and snow-covered regions, critical to climate studies.